The Issue of Spiritual and Moral Education in the Peoples of the East - o’g’li, Ibodov Amirshah Ibrahim (International Journal on Human-Computing Studies, 2023)
In this article The issue of spiritual and moral education in the peoples of the East has been scientifically and theoretically analyzed.